2021
DOI: 10.1371/journal.pntd.0008983
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and associated factors among HIV positive patients after completion of treatment for Cryptococcal meningitis

Abstract: Background Cryptococcal meningitis (CCM) remains one of the leading causes of mortality among HIV infected patients. Due to factors such as the severity of CCM pathology, the quality of life (QOL) of patients post-treatment is likely to be poor. Few studies have reported on QOL of CCM patients post treatment completion. We used data collected among patients in the CryptoDex trial (ISRCTN59144167) to determine QOL and associated factors at week 10 and six months from treatment initiation. Methodology CryptoDe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Mortality remains high in the first 6 months after diagnosis of cryptococcal meningitis, and there is a high prevalence of concurrent disability and neurocognitive impairment within the first 6 to 12 months after diagnosis 40,199 . Quality of life assessment among individuals having completed treatment for cryptococcal meningitis revealed that those with a self-perceived low quality of life at week 10 after diagnosis had a higher mortality rate within the first 6 months compared to those with higher self-perceived quality of life at week 10 after diagnosis 200,201 . Data on long term (one year and beyond) quality of life are needed.…”
Section: [H1] Quality Of Lifementioning
confidence: 99%
“…Mortality remains high in the first 6 months after diagnosis of cryptococcal meningitis, and there is a high prevalence of concurrent disability and neurocognitive impairment within the first 6 to 12 months after diagnosis 40,199 . Quality of life assessment among individuals having completed treatment for cryptococcal meningitis revealed that those with a self-perceived low quality of life at week 10 after diagnosis had a higher mortality rate within the first 6 months compared to those with higher self-perceived quality of life at week 10 after diagnosis 200,201 . Data on long term (one year and beyond) quality of life are needed.…”
Section: [H1] Quality Of Lifementioning
confidence: 99%